การเปรียบเทียบผลึกเชิงเดี่ยว YSO, LYSO และ LSO ที่เจือด้วย Ce3+ สำหรับการตรวจวัดรังสีแกมมา Comparison of YSO, LYSO and LSO Single Crystals Doped with Ce3+ for Gamma Ray Detection - พันธุ์พฤกษ์ อัคคพงศ์; ทองพูล วรนุศย์ (Science Essence Journal, 2016)
บทคัดย่อ บทความนี้ คณะผู้วิจัยได้เปรียบเทียบคุณลักษณะซินทิลเลชันของผลึก 3 ชนิด ได้แก่ YSO(Ce), LYSO(Ce) และ LSO(Ce) ผลึกที่ถูกศึกษาทั้งหมดผลิตจาก 3 บริษัทในประเทศสาธารณรัฐประชาชนจีน ผลึก YSO(Ce) แสดงค่าแยกชัดพลังงานที่ดีที่สุดคือประมาณ 9.1% ซึ่งดีกว่า 11.3% และ 10.6% ที่ได้จากผลึก LYSO(Ce) และผลึก LSO(Ce) ตามลำดับ สำหรับที่พลังงาน 662 keV ผลึก LSO(Ce) และ LYSO(Ce) แสดงปริมาณแสงที่เปล่งออกมาใกล้เคียงกัน ในขณะที่ผลึก YSO(Ce) เปล่งแสงออกมาน้อยที่สุด ในช่วงพลังงานตั้งแต่ 31 keV ถึง 1,333 keV ความเป็นสัดส่วนของยิลด์แสงต่อค่าพลังงานรังสีแกมมาของผลึกทั้งสามได้ถูกวัด ค่าโฟโตแฟรกชันโดยประมาณของผลึกทั้งสามได้ถูกรายงานและเปรียบเทียบกับค่าอัตราส่วนของภาคตัดขวางที่คำนวณด้วยโปรแกรม WinXCom ABSTRACT In this paper, we compared scintillation characteristics of three types of crystals, namely YSO(Ce), LYSO(Ce) and LSO(Ce). All studied crystals were supplied by three companies in P.R. China. The YSO(Ce) sample shows the best energy resolution of about 9.1% which is better than 11.3% and 10.6% for the LYSO(Ce) and LSO(Ce) samples, respectively. For a gamma ray energy of 662 keV, the LSO(Ce) and LYSO(Ce) samples show comparable light output, while the YSO(Ce) sample is the worst. Over the energy range of 31-1,333 keV, the light yield proportional characteristic versus gamma ray energy of all the samples was measured. The estimated photo-fraction of all tested samples was reported and compared to the cross-sectional ratio computed using the WinXCom program.